Immune-associated plasma proteins in oral and oropharyngeal cancer patients - Supranee Buranapraditkun; Patnarin Mahattanasakul; Areeya Diloktaweewattana; Narumol Bhummaphan; Chutha Siriwattanakankul; Fardeela Bin-Alee; Napadon Tangjaturonrasme; Apiwat Mutirangura; Nakarin Kitkumthorn (Heliyon, 2022)
Background: Plasma protein patterns differ between cancer patients and healthy donors. This study aimed to examine the plasma levels of several cytokines and immunological checkpoint proteins between patients with oral and oropharyngeal cancer and healthy donors. Materials and methods: Plasma samples from healthy donors, oral cancer patients, and oropharyngeal cancer patients were analyzed using the Human Th Cytokine Panel 13-plex (IL-2, 4, 5, 6, 9, 10, 13, 17A, 17F, 21, 22, IFN-γ, and TNF-α) and Human Immune Checkpoint Panel1 12-plex [sCD25 (IL-2Ra), 4-1BB, sCD27, B7.2 (CD86), Free Active TGF-β1, CTLA-4, PD-L1, PD-L2, PD-1, Tim-3, LAG-3, and Galectin-9]. The plasma 4-1BB levels were verified by Western blot method. In addition, the study of the receive operating curve (ROC) yielded the calculation of a number of diagnostically significant indicators. Results: Significantly increased levels of IL-6, 4-1BB, PDL-1, PD-1, and CTLA-4 and decreased levels of IL-13 and sCD27 were observed in cancer patients compared with healthy donors. These levels were highly significant, particularly for cancer patients in stage IV. Validation by Western blot revealed that cancer patients had higher plasma levels of 4-1BB than healthy donors (p < 0.05), and ROC curve analysis revealed that plasma 4-1BB had the highest cancer detection capability. Intriguingly, plasma levels of 4-1BB were significantly positively correlated with PDL-1 and PD-1 levels (p < 0.0001). Conclusion: This data provided descriptive knowledge of oral and oropharyngeal cancer immunity at a fundamental level. Additional research should concentrate on the significantly different factors, especially 4-1BB, PDL-1, and PD-1, which may contribute to the development of novel alternative diagnostic tools or therapies for patients with oral and oropharyngeal cancer.